100 Ideeën voor Caribische regelgevers Een praktijkgids - Konijnenbelt, Willem (Amsterdam University Press, 2022)
This book fits into the (limited in scope) Dutch tradition of university research and publications on 'good lawmaking'. It takes into account the specific needs and possibilities of 'small island countries' with a limited administrative system and where the language of the legal regulations is different from the colloquial language of the majority of the population and civil servants. It builds on an earlier, somewhat similar work by the author, 100 Ideas for the Municipal Regulator (3rd Dr. 2018).